Development and Implementation of WhatsApp-based Health Literacy Media for Pregnant Women (Rakes Bumil): A Community Empowerment Approach using ADDIE and AIDA Models - Nurullinisa, Wulan; Ciptaningtyas, Ratri; Alkaff, Raihana Nadra; Nurrizka, Rahma Hida (Applied Research in Science and Technology, 2025)
Background: Pregnant women in urban areas are used to accessing digital information, but not all of it is easy to understand, especially for those with low health literacy. A survey in Bogor District showed that 27.5% of pregnant women have problematic literacy. WhatsApp, as a commonly used platform, has the potential to be an interactive educational media. Using the ADDIE stages and the AIDA strategy, the media was designed to deliver clear and engaging messages.Aims: This study aims to develop and implement WhatsApp-based Rakes Bumil educational media with ADDIE stages and AIDA strategies to deliver accurate and interesting health information, to encourage an increase in the health literacy of pregnant women, especially in the aspects of knowledge, search, assessment, and decision making related to pregnancy health information.Methods: This study uses a quantitative approach with participatory action research design for content validation and development, implementation of Rakes Bumil educational media following the ADDIE model and AIDA strategy.Result: The media was developed through ADDIE stages, in Rakes Bumil there are ChatBot media, flyers, animated videos, and interactive quizzes. The feasibility test results show that the media is well received by pregnant women, with >90% of pregnant women stating that the media is feasible to use to support pregnancy literacy. The 14-day implementation showed an increase in engagement and understanding of health information. These findings form the initial basis for further research that will quantitatively evaluate the effectiveness of the media.